A Preliminary Study: The Effects of Vaginal Flushing in Cattle on Mitigating Vaginitis Induced by a Controlled Internal Drug Release (CIDR) - Sydney B Noel (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objective was to characterize CIDR-induced vaginitis in beef heifers by quantifying inflammatory cells and evaluating if flushing the vagina with a saline solution after CIDR removal reduces polymorphonuclear leukocyte (PMN) cells on day 10 compared to unflushed heifers. Study Description: Beef heifers (n = 19) from the Kansas State University Heifer Development Unit were stratified by weight and randomly assigned to CIDR+Flush (n = 7), CIDR (n = 7), or control (n = 5). Vaginitis scores were given visually. Vaginal cytology samples were collected with sterile swabs and analyzed on days 0, 7, and 10. On day 7, the CIDRs were removed, vaginitis scores assessed, and a sterile saline solution was used in the CIDR+Flush group to lavage the vagina at CIDR removal in conjunction with using a Metricheck device to remove the flush from the vagina. The Bottom Line: CIDR-induced vaginal inflammation is an issue in yearling heifers. Using strategies to indicate when PMN levels are greatest could optimize interventions and improve reproductive outcomes.
Keywords: vaginitis; heifers; CIDR